View dependent simplification on out-of core datasets in 3D realtime game engine development - Tan, Kin Heok (Penerbit UTM, 2008)
Rapid technology growth in modern 3D scanning technology and the high complexity of computer simulations have led to a boost in the size of geometry data sets. Even the most powerful graphics hardware also is not able to handle the rendering of the extremely massive data. Noticeable delay or jagged effects always bother the rendering quality. It is significant especially in real-time and interactive application. The conventional simplification approaches are no more sufficient to handle it. Thus, outof- core approach is invented. Besides, in many applications, surface attributes are important to show the details of the mesh. Therefore, automatic simplification is done on massive datasets while preserving its surface attributes. In this chapter, we present a preliminary approach to represent the data in an Octree structure and then to simplify the model using modified memory insensitive technique. During run-time, the portion of the visible mesh will be rendered view-dependently.